VD_FINDINFO Arrêt / 2024 / 708 vom 20. August 2024 - VD Tribunal cantonal (2024)
OPÉRATION DE CHIRURGIE COSMÉTIQUE, DÉFIGURATION, AM, CARACTÈRE DE MALADIE | 24 LAMal, 25 al. 1 LAMal, 32 LAMal, 33 al. 1 LAMal, 3 LPGA, 33 OAMal